Personalized diet and exercise recommendations in early rheumatoid arthritis: A feasibility trial. (2nd October 2017) - Garner, Stephanie; Fenton, Tanis; Martin, Liam; Creaser, Caitlin; Johns, Carolyn; Barnabe, Cheryl
Abstract: Background: Physical activity and diet have a positive influence on disease activity and cardiovascular risk in patients with rheumatoid arthritis (RA). Objective: We tested the feasibility and effect of a brief individualized counselling intervention on physical activity levels and fitness, and dietary intake, compared with standard of care. Methods: Thirty patients with inflammatory arthritis (<1 year duration) were assigned to standard of care or the intervention, which consisted of individualized visits with a dietetic intern and physiotherapist at two time points, to review age‐specific strategies on diet and exercise. Primary outcomes included anthropometric measurements (height, weight, waist and hip circumference), nutritional intake, physical activity (pedometer steps) and physical fitness. Disease activity measures and biochemical testing (blood pressure measurement, inflammatory markers, cholesterol profile and random glucose) were collected. The changes in these outcomes from baseline to 6 months were assessed using paired t‐tests between groups. Results: Thirteen patients in the intervention group and 10 in the control group completed the study. There were non‐significant trends in improvements in physical activity, low‐density lipoprotein cholesterol level and nutritional intake (vitamin C, iron, fibre, vitamin A and folate) in the intervention group. Conclusions: Poor enrolment and high dropout rates in this short‐term study highlighted the difficulty of behavioural change. Those continuing in the study and who received the intervention demonstrated a non‐significantly improved activity level and nutritional intake that may benefit long‐term outcomes.